Quality management and competitiveness, the diffusion of the ISO 9000 standards in Latin America and recommendations for government strategies - Schuurman, Hessel (UN SantiagoCL, 1997)
Seeks to demonstrate the importance of quality in national strategies for increased productivity and competitiveness. Focuses on the ISO 9000 standards for quality management systems.